Multimodality Monitoring: Toward Improved Outcomes - Gandee, Richard; Miller, Chad (Seminars in Respiratory and Critical Care Medicine, 2017)
Multimodality monitoring provides insights into the critically ill brain-injured patient through the assessment of biochemical, physiological, and electrical data that provides insight into a patient's condition and what strategies may be available to limit further damage and improve the odds for recovery. Modalities utilized include evaluation of intracranial pressure along with cerebral perfusion pressure to determine adequate blood flow; continuous electroencephalography to protect the patient from seizures and to identify early functional manifestations of ischemia and toxicity; transcranial Doppler evaluation for bedside review of circulatory adequacy; tissue oxygen monitoring to establish that brain tissue is receiving adequate oxygen from blood flow; and microdialysis to evaluate the metabolic function of the tissue in areas of concern. These monitors provide insights regarding specific aspects of brain tissue and overall brain function in the critically ill patient. Although recommendations continue to evolve for therapeutic targets for each of these modalities, an effective clinician may use each of these modalities to evaluate patients on an individual basis to improve the outcome of each patient, tailoring management to provide the care needed for any unique clinical presentation.
Keywords: multimodality monitoring; neurocritical care; brain injury; extraventricular drain; transcranial Doppler; Licox; cEEG